Tiny Non-coding RNAs in Body Fluids, Possible Biomarkers for Autosomal Dominant Polycystic Kidney Disease (Iranian Journal of Kidney Diseases, 2019)
The functional and structural disease with autosomal dominant inheritance (ADPKD) shows a poly cystic nature is described by the presence of epithelial cysts in the human renal parenchyma. There are no standard and reliable biomarkers for the detection of ADPKD in early stages which delays the therapeutic approaches. Ideal biomarkers of ADPKD, should have high sensitivity, specificity, and excellent association with disease pathogenesis and development. Both in vitro cellular and in vivo studies on animal models proved the significant roles of miRNAs in the course of ADPKD. In addition, different studies have explored miRNAs up or down regulation both in renal tissue and extracellular fluids in ADPKD which represent novel indicators applicable for diagnosis or targeted therapy. Since urine is a non-invasive, easily accessible sample for ADPKD, it could be the best sample for diagnosis. Additionally, due to early action of miRNAs for regulation the gene expression or because of their unique chemical properties, detectable urine miRNAs can be employed as appropriate biomarkers for timely diagnosis or intensive care of the progression of renal destruction or response to treatment. In this review, the specific microRNAs involved in the pathogenesis of PKD will be discussed with a particular focus on extracellular miRNAs with possibility for application as biomarkers.